PENERAPAN PENDIDIKAN MATEMATIKA REALISTIK INDONESIA (PMRI) UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA KELAS III SD NEGERI 46 PEKANBARU - Eni Trihoti; Gustimal Witri; Otang Kurniaman (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This research is motivated by the facts found in class 3 SDN 46 Pekanbaru, which shows the results of learning mathematics is still relatively low. formulation of the problem in this research is "whether the practice of Indonesia Realistic Mathematics Education (PMRI) can improve learning outcomes math students in grades 3 SDN 46 Pekanbaru?” . The purpose of this research is to improve learning outcomes math students in grades 3 SDN 46 Pekanbaru with the practice of  Indonesia Realistic Mathematics Education (PMRI). Hypothesis in this study that if adopted the Indonesia Realistic Mathematics Education (PMRI) can improve learning outcomes math students in grades 3 SDN 46 Pekanbaru. This research was conducted in SDN 46 Pekanbaru in April 2016. This research is a class action (PTK) with two cycles. This research subject is class 3 SDN 46 Pekanbaru 2015/2016 academic year consisting of 32 students to 14 boy students and 18 girl students. Based on research results from the teacher activity sheet seen increased every meeting. The first meeting of the cycle I 72,2%. The second meeting of the cycle I 77,7%, in the fourth meeting of cycle II 88,8 % and the fifth meeting of the cycle II 97,2% cycle. Whereas the activity of students is also increasing every meeting. At the first meeting of the cycle I 63,8% the second meeting of the cycle I 72.2%. At the fourth meeting of the cycle II 83,3% and the fifth meeting of the cycle II 91.6%. Learning outcomes in the first cycle increased by 31,25% from 40,62% to the base score 71,8%. In the cycle II increased by 9,38% to 81,25%. The average value of the base score 67.31. In UH I increased to 73,02 % with an increase of 8,48%. On UH II average value increased to 84,00 % with the increasing of 15,11%. So the results of this study in according to the hypothesis of action. Key words: Indonesia Realistic Mathematics Education (PMRI), mathematics \     learning outcomes